Analysis on Mechanism to Improve the Recovery in Tight Oil Reservoirs by Imbibition. Issue 1 (June 2020) - Chunming, He; Jin, Chen; Xiaochao, Wang; Shuai, Li; Ning, Cheng; hui, Zhang
Abstract: In order to explore the mechanism to improve the recovery percent in tight oil reservoirs, the mechanisms and main controlling factors of improving the recovery percent by different production mechanisms are analyzed by combining spontaneous imbibition, core displacement experiment and nuclear magnetic resonance (NMR) test. It is shown by the study that the recovery percent can be improved from 20% to more than 40% by increasing the displacement differential pressure for tight rock samples. During differential pressure displacement, the reservoir fluid in large and medium pores is mostly produced. It is proven by the pressured imbibition experiment that in the process of soaking, the fluid exchange between fractures and matrix and between large and small pores can be realized to improve the recovery percent of fine pores, and the recovery percent (mainly of fine pores) can be improved by 7-10% through pressured imbibition displacement. Large contact area caused by the complex fractures formed by stimulated reservoir volume (SRV) fracturing is the basis to improve the recovery percent by imbibition, but the recovery percent of simple fractures is limited. The research results of this paper will provide guidance for the stimulation technology and fluid system optimization to improve the recovery percent of tight oil.